Open Reduction Assisted With an External Fixator and Internal Fixation With Calcaneal Locking Plate for Intra-articular Calcaneal Fractures. (October 2017) - Yao, Hui; Lu, Huading; Zhao, Huiqing; Lv, Lulu; Hou, Gang
Background: The extensile lateral approach (ELA) has been considered to be a standard approach for displaced intra-articular calcaneal fractures (DICF) because it provides excellent exposure and allows direct reduction of the depressed posterior facet fragment. But continuous retraction during surgery needs sufficient manpower and may cause ischemia. Failure of rigid fixation of DICF will not allow for early weight bearing and may lead to a loss of reduction. To avoid these disadvantages, this study presents open reduction assisted with an external fixator and internal fixation with a calcaneal locking plate. Methods: A series of 58 patients with 62 DICFs were treated over a period of 49 months. All patients were clinically and radiologically followed up with a mean follow-up of 35 (range 29-42) months. Clinical follow-up included visual analog scale (VAS), the American Orthopaedic Foot & Ankle Society (AOFAS) hindfoot score, and ability to work. Radiologic follow-up included axial and lateral radiographs and measurements of the Bohler angle and Gissane angle. Results: At the final follow-up, all fractures had healed. The mean VAS score was 2.9 (range 0 to 8, SD 1.9) and the average AOFAS score was 71 (range 55-85, SD 8.1). The mean postoperative Bohler angle immediately after the surgery was 28.3 degrees (range 13.0-44.6, SD 7.0), which decreased to 27.5 degrees (range 12.2-43.3, SD 7.0) at the final follow-up, and the mean postoperative Gissane angle after the surgery was 116.3 degrees (range 94.9-131.5, SD 9.0) which finally increased to 118.4 degrees (range 94.5-135.8, SD 9.3). No statistically significant differences regarding Bohler and Gissane angles were found between different Sanders fracture types ( P >.05). Conclusion: The presented operative technique was found to provide comparable reduction of Sanders type II-IV injuries. Level of Evidence: Level III, case control study.